PENGARUH FAKTOR-FAKTOR ASIMETRI INFORMASI TERHADAP INITIAL RETURN IPO DI BEI - Meylani Tuti (LPPM Universitas Asa Indonesia, 2015)
The frequent phenomenoms that occur in various countries, including the current situation in Indonesia are underpricing and overpricing, at the Initial Public Offering (IPO). Between the insider and the outsider, in which information gap the writer got interested to conduct this research. The approach being used is quantitative approach by testing the hypothesis through regression analysis. The data used are initial return, update price, company size and age, kind of industry and the reputation of the company IPO underwriter of the period of June 2005 up to may 2014. The result of the research shows the TARCH model with the threshold that shows that this is a good model of initial return, whereas the regression test result indicates that the variables of updated price, company size, company age, and kind of industry give positive and significant influence towards initial return, and the reputation of the underwriter gives negative influence towards initial return.